The complete chloroplast genome of Marupa (Simarouba amara Aubl., Simaroubaceae) - Nora Scarcelli; Carmen Garcia Davila; Marie Couderc; Diana Castro Ruiz; Guillain Estivals; Carlos Alberto Custodio Angulo Chavez; Hector Acho Vasquez; Jhon Gregory Alvarado Reategui; Tony Vizcarra Bentos; Cédric Mariac (Ecology and Evolution)
Abstract Marupa (Simarouba amara Aublet 1775) is a tropical tree of the family Simaroubaceae. It is commonly used for its wood in the Amazonian forest, and it is an important species for restoring degraded environments. Yet, very little genetic resources are available to study this plant. In this paper, we sequenced for the first time the complete chloroplast genome of Marupa, using Oxford Nanopore long‐read technology. The genome is 159,838 bp, includes 131 genes in total and presents a classic quadripartite structure. Its length and structure are similar to those of sister species of the Simaroubaceae family. A maximum likelihood phylogeny of the order Sapindale reveals that Simarouba amara is well positioned in its family. This complete plastome is a first step towards a better analysis of Marupa future evolution.